2016
DOI: 10.1111/vcp.12355
|View full text |Cite
|
Sign up to set email alerts
|

What is your diagnosis? Pituitary mass in a dog

Abstract: A 7-year-old male neutered Boston Terrier, previously diagnosed with hyperadrenocorticism, was presented to the University of Missouri Veterinary Medical Teaching Hospital Neurology service for evaluation of a large pituitary mass revealed on computer tomography (CT) and progressively worsening clinical signs despite treatment. Upon arrival, the dog's vital parameters, including heart and respiratory rate and temperature, were within normal limits. The mucous membranes were dry. The neurologic examination reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…7,[18][19][20] Pituitary neoplasms typically exhibit distinct cytologic features commonly associated with neuroendocrine tumors, including naked or free nuclei within pale cytoplasm lacking distinct borders. 11,12 However, other neoplasms or alterations described in the sellar or suprasellar regions differ significantly from those observed in pituitary adenomas within the scope of this study.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…7,[18][19][20] Pituitary neoplasms typically exhibit distinct cytologic features commonly associated with neuroendocrine tumors, including naked or free nuclei within pale cytoplasm lacking distinct borders. 11,12 However, other neoplasms or alterations described in the sellar or suprasellar regions differ significantly from those observed in pituitary adenomas within the scope of this study.…”
Section: Discussionmentioning
confidence: 58%
“…In one study, 12 postmortem cytology of a pituitary mass in a dog with hypercortisolism revealed features consistent with a neuroendocrine tumor. Subsequent histologic examination confirmed the presence of an invasive pituitary macroadenoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations